Saxophone players’ self-perceptions about body movement in music performing and learning: an interview study - Moura, Nádia (2024)
Quantitative studies demonstrate that performers’ gestures reflect technical, communicative, and expressive aspects of musical works in solo and group performances. However, musicians’ perspectives and experiences toward body movement are little understood. To address this gap, we interviewed 20 professional and pre-professional saxophone players with the aims of: (1) identifying factors influencing body movement; (2) understanding how body movement is approached in instrumental pedagogy contexts; and (3) collecting ideas about the impact of movements on performance quality. The qualitative thematic analysis revealed that musical features (i.e., musical character, dynamics) constitute a preponderant influencing factor in musicians’ body behavior, followed by previous experiences and physical and psychological characteristics. In the pedagogical dimension, participants presented an increased aware- ness of the importance of body movement compared to their former tutors, describing in-class implementation exercises and promoting reflection with their students. Still, a lack of saxophone-specific scientific knowledge was highlighted. Regarding performance quality, participants discussed the role of movement in facilitating per- formers’ execution (i.e., sound emission, rhythmical perception) and enhancing the audience’s experience. We provide insights into how professionals conceive, practice, and teach motor and expressive skills, which can inspire movement science and instrumental embodied pedagogy research.